Resource and Infrastructure-Appropriate Management of ST-Segment Elevation Myocardial Infarction in Low- and Middle-Income Countries. Issue 24 (16th June 2020) - Chandrashekhar, Y.; Alexander, Thomas; Mullasari, Ajit; Kumbhani, Dharam J.; Alam, Samir; Alexanderson, Erick; Bachani, Damodar; Wilhelmus Badenhorst, Jacobus Cornelius; Baliga, Ragavendra; Bax, Jeroen J.; Bhatt, Deepak L.; Bossone, Eduardo; et al.
Abstract : The 143 low- and middle-income countries (LMICs) of the world constitute 80% of the world's population or roughly 5.86 billion people with much variation in geography, culture, literacy, financial resources, access to health care, insurance penetration, and healthcare regulation. Unfortunately, their burden of cardiovascular disease in general and acute ST-segment–elevation myocardial infarction (STEMI) in particular is increasing at an unprecedented rate. Compounding the problem, outcomes remain suboptimal because of a lack of awareness and a severe paucity of resources. Guideline-based treatment has dramatically improved the outcomes of STEMI in high-income countries. However, no such focused recommendations exist for LMICs, and the unique challenges in LMICs make directly implementing Western guidelines unfeasible. Thus, structured solutions tailored to their individual, local needs, and resources are a vital need. With this in mind, a multicountry collaboration of investigators interested in LMIC STEMI care have tried to create a consensus document that extracts transferable elements from Western guidelines and couples them with local realities gathered from expert experience. It outlines general operating principles for LMICs focused best practices and is intended to create the broad outlines of implementable, resource-appropriate paradigms for management of STEMI in LMICs. Although this document is focused primarily on governments and organizations involved with improvement in STEMI care in LMICs, it also provides some specific targeted information for the frontline clinicians to allow standardized care pathways and improved outcomes. Abstract : Supplemental Digital Content is available in the text.